RANCANG BANGUN SISTEM GESTUR UNTUK PASIEN TIRAH BARING BERBASIS MIKROKONTROLER DAN SENSOR PAJ7620U2 - Ahmad Rafi Nur Adli (2023)
Gesture reader technology is one of the effects of the times that can help humans in a number of activities, one of which is for bed rest patients who have difficulty communicating where these patients can take advantage of a device with a microcontroller-based gesture system and sensor PAJ7620U2 to communicate with surrounding people. The Gesture System tool utilizes the ESP-NOW protocol communication technology which makes data exchange happen quickly and has been tested by taking as many as 800 data samples which show the accuracy and precision of the tool are 92% and 90.25% respectively.